Quality Quality Education and Educational Facilities in Secondary Schools: A Nexus - Javed, Muhammad Latif; Barirah Ishaq; Muhammad Nadeem Javed (Pakistan Journal of Humanities and Social Sciences, 2021)
This study examines the educational facilities which are important in providing quality education at secondary schools. The researcher examined the appropriateness of physical infrastructure, teaching-learning material, library, computer laboratory, and science laboratory at secondary schools to find out nexus of quality education with these provided educational facilities. The research design of the study was quantitative in nature. The research population included 194 secondary schools in Bahawalnagar, 194 head teachers, and 3739 SSTs. The sample of the study was comprised of over 45 head teachers and 90 sets of all the secondary schools of Tehsil Bahawalnagar selected by using cluster random sampling technique. A questionnaire was developed on a 5- point Likert scale to examine & analyze the educational facilities including teaching-learning material, computer laboratory, and library and science laboratory. An observation checklist was also developed and used for the collection of data. The further checklist was divided into three options yes, no and status further divided into two options useable and unusable, appropriateness, and inappropriateness. Data was collected & analyzed using descriptive statistics including percentage and frequency to examine the appropriateness of educational facilities. Quantitative data was analyzed using computer-generated software SPSS. Results revealed that the majority of the respondents were agreed with educational facilities. The study concludes that the researcher observe the educational facilities through a checklist maximum facilities were present, useable and appropriateness of these was also registered. Research study recommended that more opportunities for students may be available for experience science being exposed to more practical’s work in labs which may enhance better performance in science subjects.